Organisational culture affecting post-merger integration: New insights from Chinese reverse M&As in Germany. Issue 2 (3rd June 2019) - Yang, Yanan; Lütge, Christoph; Yang, Hongwei
Abstract : Purpose: The purpose of this paper is to determine the principal organisational cultural dimensions that affect levels of post-merger integration (PMI) in Chinese acquisitions in Germany and to explore the relationship of these specific organisational cultural dimensions and levels of integration. Design/methodology/approach: Data set were collected using a structured questionnaire given to Chinese and German managers and employees, who implemented/were responsible for the PMI in 12 Chinese acquisitions in Germany. A total of 120 questionnaires were distributed and there were 67 respondents, corresponding to a response rate of about 56 per cent. Principal components analysis, one-way ANOVA and bi-variate Spearman's correlation were applied to analyse the data. Findings: Findings revealed that five organisational cultural dimensions (i.e. adaptability, consistency, involvement, balance and flexibility) were extracted to be the primary indicators affecting levels of integration in Chinese reverse mergers and acquisitions (M&As) in the German market. Further, adaptability emerged as the only predictor with a significant negative implication on predicting the degree of PMI that Chinese investors would initiate to integrate their acquired German subsidiaries. Originality/value: This study is one of the few studies to consider the specific organisational cultural dimensions affecting the integration levels of reverse M&As and is the first study, to the best of our knowledge, to explore the correlations of specific corporate cultural dimensions and integration levels in emerging multinational enterprises' reverse M&As through quantitative research.